Temporal Variation in the Ecological Functioning of Benthic Communities After 20 Years in the Eastern Mediterranean - Tsikopoulou, Irini; Dimitriou, Panagiotis D.; Karakassis, Ioannis; Lampadariou, Nikolaos; Papadopoulou, Nadia; Smith, Christopher J. (Frontiers in Marine Science, 2021)
Marine benthic ecosystems face well documented changes as a result of human activities. Describing these changes is important for predicting ecosystem functioning. In this context, long-term changes in soft-bottom macrofaunal communities after a quarter of a century were studied in the south Aegean Sea with the purpose of investigating whether temporal changes in taxa diversity are accompanied by changes in functional diversity, and secondly to determine the main mechanisms driving these changes (i.e., deterministic versus stochastic processes). To achieve this, a large data set that included species abundance data collected in 1990 and 2014 from several sampling sites along a transect line was used. A biological trait analysis (BTA) was conducted to determine the species functional roles. The results revealed a decline in taxonomic alpha and beta diversity metrics between 1990 and 2014. A difference that was also reflected in functional richness but not in functional redundancy and functional composition. The stability of functional composition indicated that replacements of functionally similar taxa may occur, ensuring the resilience of the ecosystem to provide goods and services. Finally, the comparison of co-occurrence and functional networks for 1990 indicated a non-differentiation with the null model and, it was not possible to determine if the benthic community was structured due to stochastic processes (e.g., dispersal, natural disasters) or an overlap of deterministic processes (e.g., niche-filtering, competition). In contrast, the comparison of networks for 2014 pointed out that environmental conditions have acted as a major filter on species distribution.